PERAN PEREMPUAN DALAM PELAYANAN GEREJA DI STASI LANDONANGA PAROKI MAXIMILIANUS MARIA KOLBE - Ndae, Angelina Marici Darsan; Widyawati, Fransiska; Lon, Yohanes Servatius (CREDENDUM: Jurnal Pendidikan Agama, 2025)
The Church as the People of God presupposes the active engagement of every member, especially within local communities such as parishes and stations. Women, as integral members of the Church, are likewise called to participate fully in parish life. This descriptive study examines the role of women in church ministry at the Maximilianus Maria Kolbe Parish specifically at the Landonanga Station in the Diocese of Ruteng by investigating the service tasks they perform, the significance of their ministries, parish responses to their contributions, how they understand their service as members of the People of God, and the sources of support that sustain their work. Using a qualitative approach, data were collected through interviews and document analysis. The findings reveal that women serve in parish and station leadership as committee members, although they have not yet assumed the highest council leadership position. They contribute across various parish commissions and engage in all five dimensions of church ministry liturgy, kerygma, diakonia, coinsonia, and martyria. Their service is positively received and acknowledged by both church authorities and the laity, yet they encounter challenges such as patriarchal cultural norms and the burden of dual responsibilities. The study concludes that while women already play a vital role in church ministry and enjoy considerable support, they continue to face significant obstacles. This research thus enriches our understanding of women's contributions to local church life, highlighting both the enablers and barriers that shape their ministry.